ANALISIS PENGARUH PROFITABILITAS DAN KUALITAS AKTIVA PRODUKTIF TERHADAP KEPERCAYAAN INVESTOR DI BANK BNI PERIODE 2014 – 2024 - Miftakhus Sa’adah; Tri Wartono (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to determine and analyze the effect of Return on Assets (ROA) and Non-Performing Loans (NPL) on Stock Prices at Bank Negara Indonesia (Persero) Tbk for the period 2014–2024. This type of research is quantitative research using secondary data obtained from financial reports published through the official websites www.idx.co.id and www.bni.co.id. Data analysis techniques used include classical assumption tests (normality test, heteroscedasticity test, autocorrelation test, and multicollinearity test), multiple linear regression analysis, coefficient of determination (R²) test, and hypothesis testing (t-test and F-test). The results of the study indicate that partially, the variables Return on Assets (X1) and Non-Performing Loans (X2) do not have a significant effect on Stock Prices (Y). This is indicated by the ROA significance value of 0.1497 > 0.05 with a calculated t value of 1.593571 < t table 2.30600, as well as the NPL significance value of 0.0594 > 0.05 with a calculated t of 2.196061 < t table 2.30600. While simultaneously, the ROA and NPL variables also do not have a significant effect on Stock Prices, with a significance value of 0.126039 > 0.05 and a calculated F value of 2.713266 < F table 4.46. Thus, it can be concluded that ROA and NPL do not have a significant effect either partially or simultaneously on the stock price of Bank Negara Indonesia (Persero) Tbk during the 2014–2024 period.